2014
DOI: 10.1094/cchem-02-13-0032-r
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Roll Gap, Kernel Shape, and Moisture on Wheat Breakage Modeled Using the Double Normalized Kumaraswamy Breakage Function

Abstract: Flour milling separates endosperm from bran through repeated roller milling and sifting, in which the size distribution of particles produced by the initial breakage of the wheat kernels critically affects the process. The double normalized Kumaraswamy breakage function (DNKBF), previously developed to describe wheat breakage during roller milling, was extended to refine the modeling of the effect of roll gap on breakage. The DNKBF describes two populations of particles arising from roller milling of wheat, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…7B). Previous work similarly found that soft wheats under D-D were the least well behaved in terms of the adequacy of the DNKBF (Campbell et al 2012), particularly in accounting for effects of roll gap (Fuh et al 2014). Overall, however, it could be concluded that the DNKBF described the experimental data well and allowed effects of debranning on first break milling of wheat to be distinguished and quantified.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…7B). Previous work similarly found that soft wheats under D-D were the least well behaved in terms of the adequacy of the DNKBF (Campbell et al 2012), particularly in accounting for effects of roll gap (Fuh et al 2014). Overall, however, it could be concluded that the DNKBF described the experimental data well and allowed effects of debranning on first break milling of wheat to be distinguished and quantified.…”
Section: Resultsmentioning
confidence: 85%
“…Previous work concluded that, for whole wheats, the relationship between milling ratio and output particle size was approximately a square root relationship (a = 0.5) under D-D and slightly less than a square root relationship (a = 0.4) under S-S for a wide range of wheat hardnesses (Campbell et al 2012;Fuh et al 2014). In so doing, it allows the relationship between the milling ratio and the output particle size to be quantified.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Cultivation methods, such as tillage, are also thought to have contributed to grain size increases as bigger seeds could tolerate sowing at increased depths and therefore be selected for indirectly (Zohary et al, 2012). In addition, food processing methods may have led to selection for grains with bigger endosperm as they would be easier and more profitable to mill (Fuh et al, 2014). Alternatively, larger grains could have arisen via pleiotropic effects or genetic linkage and driven by selection that favoured larger organs and plants (Kluyver et al, 2017).…”
Section: Introductionmentioning
confidence: 99%